Medicinal Study of Indigenous Plants of Family Leguminosae on Bronchial Asthma - Khare, M.L.; Saxena, R.C.; Shukla, Deepti; Raghuwanshi, Pramendra; Paliwal, Anurag (Asian Journal of Chemistry, 2010)
Tephrosia purpurea has been used in ayurvedic system of medicine for asthma and various other diseases. The crude powdered material in two different doses of 250 mg/day for a months period, given orally, has cured persons belonging to different age-groups suffering from chronic bronchial asthma without any side effect. An effort has been made to give a scientific view to the folk medicine used in villages and tribal pockets of India. As such 70% ethanolic extract prepared by soxhleting the dried powdered material of the whole herb showed a 'saponin' like compound based on preliminary screening tests. The complete chemical structure of the compound is yet to be determined.